How Well Prepared Are We for the Next Pandemic? (KULT_online, 2024)
Since COVID-19, pandemic preparedness has become an urgent global issue. Carolin Mezes’ dissertation addresses key issues in the monitoring of past pandemic preparedness, such as establishing accountability practices and strengthening health system capacity. The author analyzes public health emergencies from a cultural and infrastructure perspective, which helps clarify what went wrong in the past in order to pave the way for a safer future.